2019
DOI: 10.1111/are.14355
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin‐supplemented high‐soya bean meal diets of juvenile black sea bream, Acanthopagrus schlegelii : Study on growth performance and intestinal morphology and structure

Abstract: An 8‐week growth trial was conducted to evaluate the effects of different levels of tributyrin supplementation in a high‐soya bean meal diet on juvenile black sea bream (11.30 ± 0.16 g). The positive control (PC) diet contained 45% fishmeal and 20% soya bean meal, while the negative control (NC) contained 12% fishmeal and 45% soya bean meal. Graded levels of tributyrin were added to the NC diet at 0.05% (TB 0.05), 0.1% (TB 0.1), 0.2% (TB 0.2), 0.4% (TB 0.4) and 0.8% (TB 0.8). Ultimately, the fish fed the PC di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 66 publications
(85 reference statements)
15
43
0
Order By: Relevance
“…Among the plant-based dietary groups, the activities of digestive enzymes were ameliorated by the increasing TB supplementation level. These results are in line with the recent findings of Volatiana, Wang, et al (2020), who reported that the intestinal protease, lipase and amylase activities were significantly increased in the black sea bream fed the TB-supplemented diets. In the study with snakehead, the greatest protease and lipase activities were observed in the TB-supplemented groups compared with these in chromium yeast groups and bile acid groups (Hou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the plant-based dietary groups, the activities of digestive enzymes were ameliorated by the increasing TB supplementation level. These results are in line with the recent findings of Volatiana, Wang, et al (2020), who reported that the intestinal protease, lipase and amylase activities were significantly increased in the black sea bream fed the TB-supplemented diets. In the study with snakehead, the greatest protease and lipase activities were observed in the TB-supplemented groups compared with these in chromium yeast groups and bile acid groups (Hou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Dietary TB also has been reported to positively affect the growth performance of snakehead (Hou et al, 2019). Recent studies showed that an appropriate dietary TB level improved the growth performance of black sea bream (2.0 g kg −1 -4.0 g kg −1 ) and yellow drum (1.0 g kg −1 -2.0 g kg −1 ) fed high-soya bean meal diets (Tan et al, 2020;Volatiana, Wang, et al, 2020). Similarly, other butyrate products with proper levels (Gao et al, 2011) and giant grouper (Epinephelus lanceolatus) (Lin & Cheng, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The liver samples were stained by Oil Red O following the processes introduced by Volatiana et al (33) . The slide microphotography was observed using an Olympus CX21 microscope.…”
Section: Histological Observationmentioning
confidence: 99%
“…As an esterification product of butyric acid and glycerol, tributyrin was slowly hydrolysed into butyric acids in the entire intestine by pancreatic lipase (Conley et al, ). However, investigation on the effects and mechanisms of tributyrin supplementation in high‐SBM diet on growth performance and intestine health is rare in aquatic animals (Volatiana et al, ).…”
Section: Introductionmentioning
confidence: 99%